THE ART OF TEACHING ISLAM THROUGH EXTRACURRICULAR CALLIGRAPHY ACTIVITIES AT KEDUNGWARU KIDUL 1 PUBLIC ELEMENTARY SCHOOL IN DEMAK REGENCY - Umamah, Naila Farikhatun; Wijayanto, Wasis (ANDRAGOGI, 2024)
Calligraphy is one of the works of Islamic art that is in the spotlight of many Muslim communities. Calligraphy is the art of beautiful writing, also called Khat. It is beautiful to carve the names of Allah SWT as a form and feeling to remember His Lord more. One of the extracurricular activities that some students are interested in is calligraphy, which helps develop their interests and talents. This research analyzes students' talents through extracurricular calligraphy activities to optimize and motivate Islamic Religious Education (PAI) learning at Kedungwaru Kidul 1 Public Elementary School (SDN Kedungwaru Kidul 1). This research uses a qualitative description method. The data collection techniques used are interviews, observation, and documentation. The results of this research in extracurricular activities or additional hours for students can increase and optimize the potential of students' talents to achieve academic and non-academic achievements, and motivate them to learn PAI. Apart from that, in the development process, the role of teachers and parents is very important for students.